If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -18 + -5x + -20 = 6 Reorder the terms: -18 + -20 + 6x + -5x = 6 Combine like terms: -18 + -20 = -38 -38 + 6x + -5x = 6 Combine like terms: 6x + -5x = 1x -38 + 1x = 6 Solving -38 + 1x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38' to each side of the equation. -38 + 38 + 1x = 6 + 38 Combine like terms: -38 + 38 = 0 0 + 1x = 6 + 38 1x = 6 + 38 Combine like terms: 6 + 38 = 44 1x = 44 Divide each side by '1'. x = 44 Simplifying x = 44
| 6x-18-5x+20=6 | | 90x+10+8x+2=-19 | | (5x-4)(x-7)=(1-4x)(x+1) | | (3x+2)(x+1)=(2x-1)(x+6) | | x^2-4x-12=x^2-3x+2 | | 9x-9=54x+216 | | 45x+225=0 | | 3x+5=7x-35 | | 6x-9=11x+26 | | 6x-4/5=10 | | 3x+5/x-5=7 | | 5x+25=3x+39 | | 5x+25=3x-19 | | 6.9x^2=0 | | 4/3+1=2/3+2n | | x-1/4x=120 | | h=16/9 | | 4p+6r= | | x+x+6+2x=94 | | (4x+4)(5x+6)=0 | | x+5x=2838 | | p^2+5p+2=0 | | x=162/11 | | -6/3= | | 31/5/81/3 | | x*23=9 | | -2(5+4x)=18 | | 120/135 | | 50x=(x/3)+10 | | 896/624 | | -5(2x-3)=12 | | 7/3= |